A Polymorphic Gold(III) Complex Comprising a Multifunctional Triazolylpropanamide Ligand. Issue 5 (23rd February 2018) - Liebing, Phil; Wang, Ling; Gilje, John W.; Kühling, Marcel; Edelmann, Frank T.
Abstract : Reaction of HAuCl4 · 4H2 O with the multifunctional ligand 3‐(1 H ‐1, 2, 4‐triazol‐1‐yl)propanamide (1, TPA) afforded the polymorphic gold(III) complex AuCl3 (TPA) (2 ) in 75 % yield. Thermal decomposition of the latter revealed the hydrochloride [HTPA]Cl (3 ). Complex2 forms a stable monoclinic and a metastable triclinic modification. The crystal structures of both modifications feature infinite supramolecular assemblies formed by secondary Au··· Cl bonding interactions and hydrogen bonding. Abstract :